2017
DOI: 10.1002/qj.3097
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of ground‐based GNSS Zenith Total Delay observation errors and their correlations using the Met Office UKV model

Abstract: Ground‐based GNSS Zenith Total Delay (ZTD) observations have been assimilated into the Met Office numerical weather prediction (NWP) models since 2007, and into the Met Office UKV model since its introduction in 2009. The UKV model is a 1.5 km resolution convective‐scale model and uses a 3D‐Var assimilation system. There is a plan to upgrade the UKV assimilation system from 3D‐Var to 4D‐Var in the near future, giving the opportunity to increase the temporal resolution of ZTDs assimilated. The ZTD observation‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The observation error and precipitable water showed a similar seasonal variation, and the observation error in summer was approximately 2.1 times larger than that in winter. In contrast with a study using the same observation error for each season and station (Bennitt et al 2017), utilizing different observation errors for different seasons or months was considered to be more appropriate for the Korean climate. Three one-month experiments were performed on the LDAPS using data from July 2016 for stable quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation error and precipitable water showed a similar seasonal variation, and the observation error in summer was approximately 2.1 times larger than that in winter. In contrast with a study using the same observation error for each season and station (Bennitt et al 2017), utilizing different observation errors for different seasons or months was considered to be more appropriate for the Korean climate. Three one-month experiments were performed on the LDAPS using data from July 2016 for stable quality.…”
Section: Discussionmentioning
confidence: 99%
“…These errors include measurement, observation operator (forward model), representativeness, and quality control error Waller et al 2015). In addition to devicebased errors, observation errors also occur during data processing because of the mapping functions that convert the slant path signals of multiple satellites into the zenith direction (Bennitt et al 2017;Lindskog et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the corrections were estimated as the mean values of the ZTD differences and they were subtracted from the ZTD observations that were lined up for data assimilation. Even though this method provides statistical corrections, this is a standard bias correction approach for ZTD data that proved to be successful in reducing the observations-model divergences and capturing the systematic errors between the ZTD observations and model forecasts [16,[18][19][20][21][22][23][24][25]28]. The last stage of the ZTD data pre-processing included a selection algorithm based on the following conditions: (a) The formal ZTD error to be lower than the standard deviation of the difference between the observed and modeled ZTD, (b) the ZTD difference between observations and model output to be lower than five times the ZTD formal error, and (c) the difference between the receiver height and the model's orography to be below 100 m. Similar criteria have been applied in previous studies [19][20][21][22][23][24][25].…”
Section: Data Pre-processingmentioning
confidence: 99%
“…Boniface et al [24] identified that the impact of ZTD assimilation in AROME model depends on the rainfall synoptic conditions, while Arriola et al [16] highlighted the importance of ZTD observations processing before the assimilation application. More recent studies focused on investigating different observational bias correction methods and on estimating spatiotemporal correlations of observations errors for application on ZTD data used for data assimilation [25][26][27].The literature review shows that improvements in the precipitation forecast skill may be gained by assimilating ZTD observations into NWP models. However, regional studies using the WRF modeling system are relatively rare (e.g., Rohm et al [28]), while no research focusing on Greece has ever been conducted.…”
mentioning
confidence: 99%